Coherent and incoherent channels of neutrino-nucleus reactions - Divari, P. C.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2020)
Inelastic neutrino-nucleus scattering cross sections at low and intermediate energies are investigated for currently interesting nuclei employed in neutrino-detection experiments. This is an extension to charged current processes of our previous QRPA calculations referred to neutral current neutrino/antineutrino-nucleus reactions. Our preliminary results for the reactions 56Fe(νe, e−)56Co and 40Ar(νe, e−)40K compare rather well with similar calculations obtained in the context of continuum RPA.